An Empirical Investigation on Waqf Governance Practices in Waqf Institutions in Malaysia - Muhammad Iqmal Hisham Kamaruddin; Mustafa Mohd Hanefah (Emerald Publishing Limited, 2024)
Indexed byWOS/SCOPUS/ERA